2013
DOI: 10.5432/ijshs.201230
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combined Strength and Endurance Training on Running Performance the Following Day

Abstract: This study examined running economy (RE) during a two-stage incremental protocol that was combined into an endurance training session 6 hours following a strength training session. In addition, this study investigated running performance which consisted of a two-stage RE protocol and time to exhaustion (TTE) the day after strength and endurance training sessions undertaken on the same day. Twelve trained and moderately trained male runners performed strength and endurance training sessions 6 hours apart with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Previous studies have shown attenuation in running performance in conjunction with a reduction in muscle force generation capacity (Chen et al, 2009;Chen, Nosaka, & Tu, 2007;Marcora & Bosio, 2007). For example, a previous study (Doma & Deakin, 2013a) showed impaired RE with a concomitant reduction in maximal isometric force the day after strength-and endurance-training sessions. Furthermore, alterations in lower-extremity kinematics were found, suggesting that strength-and endurance-training sessions on the same day may have caused detrimental effects on neuromuscular function and, as a result, attenuated movement efficiency and concomitantly increased energy C R .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have shown attenuation in running performance in conjunction with a reduction in muscle force generation capacity (Chen et al, 2009;Chen, Nosaka, & Tu, 2007;Marcora & Bosio, 2007). For example, a previous study (Doma & Deakin, 2013a) showed impaired RE with a concomitant reduction in maximal isometric force the day after strength-and endurance-training sessions. Furthermore, alterations in lower-extremity kinematics were found, suggesting that strength-and endurance-training sessions on the same day may have caused detrimental effects on neuromuscular function and, as a result, attenuated movement efficiency and concomitantly increased energy C R .…”
Section: Discussionmentioning
confidence: 95%
“…Based on a 2 K. DOMA AND G. DEAKIN nomogram for the estimation of measurement error via use of CV (statistical power of 90%; Atkinson & Nevill, 2006), percentage worthwhile differences of the current sample size (n ¼ 12) for C R , RPE, torque production, and TTE were found to be 3%, 4.5%, 10%, and 11%, respectively. These numbers are smaller than those in previous reports that have shown statistically significant differences in C R , RPE, torque production, and TTE (Doma & Deakin, 2013a;Doma & Deakin, 2014;Doma et al, 2015). In addition, an a-priori power calculation was conducted for the key dependent variables based on previous studies on male and female participants (Braun & Paulson, 2012;Doma & Deakin, 2013b;Marcora & Bosio, 2007) and showed that a sample size of 12 is sufficient to provide greater than 80% of power at an alpha level of .05.…”
Section: Participantsmentioning
confidence: 93%
“…Indeed, the neuromuscular system is considered to be one of the most important regulators of running performance (Assumpcao Cde, Lima et al Furthermore, it has been postulated that EIMD may attenuate the economy of movement and accelerate the onset of fatigue during running by altering neural recruitment patterns (Chen et al 2007), reducing stretch-shortening cycle utilisation (Chen et al 2007) and compromise proprioceptive feedback thereby altering running gait patterns (Doma and Deakin 2013b). In fact, a single bout of resistance training exercises has been reported to acutely reduce lower body ROM during running (Chen et al 2007;Doma and Deakin 2013b), with suggestions that neuromuscular fatigue, muscle soreness and EIMD possibly result in kinematic changes and impaired movement efficiency (Chen et al 2007;Doma and Deakin 2013a;Doma and Deakin 2013b). Whilst the current study did not examine running gait patterns, the reduction in ABD-ROM suggests that lower extremity ROM may have been limited during running performance as other studies have also reported that impaired sub-maximal and maximal running performance were accompanied by corresponding muscle damage-induced reduction in passive lower body ROM measures (Paschalis et al 2005;Khan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, examining the acute effects of traditional lower body resistance exercises (e.g., isoinertial concentric-eccentric exercises such as squats or leg-press exercises) on RE would improve the ecological validity from a training standpoint. Indeed, more recent studies have shown that traditional lower body resistance training exercises caused EIMD, and as a result, impaired running performance measures at both sub-maximal (Doma and Deakin 2013a; and maximal (Doma and Deakin 2013b; Doma and Deakin 2014) effort intensities for up to 48 hours post-exercise. Consequently, these findings suggest that inadequate recovery following traditional resistance training sessions may compromise the quality of subsequent endurance training sessions (Hayter et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The selection of exercises, intensity and duration of the strength training session was adapted from previous studies (Doma & Deakin, 2013a, 2014 including leg-press, leg extensions and leg PeerJ reviewing PDF | (2015:11:7825:1:1:NEW 9 Feb 2016)…”
Section: Strength Training Sessionmentioning
confidence: 99%